Improvement of the high-pressure die casting alloy Al-5.7Mg-2.6Si-0.7Mn with Zn addition - Trudonoshyn, Oleksandr; Rehm, Sebastian; Randelzhofer, Peter; Körner, Carolin (Materials Characterization, 2019)
The microstructure and mechanical properties of the high-pressure die casting alloys Al-5.7Mg-2.6Si-0.7Mn-xZn in as-cast condition have been investigated. The microstructure was studied by scanning electron microscopy (SEM), electron probe microanalysis (EPMA) and transmission electron microscopy (TEM). Intermetallic particles and volume fractions were measured using partly automated image analysis in the software Fiji/Imagej. Results of the microstructure analysis were compared with Thermo-Calc calculations. The hardness was determined by Brinell (HB) and local properties were determined by Vickers (HV0.01) testing. The ultimate tensile strength (UTS), yield strength (YS) and elongation were performed by conventional tensile tests at room temperature. The microstructure of the studied alloys consists primarily of α-Al phase, the α-AlFeMnSi intermetallics, Al–Mg2Si eutectic cells. Addition of Zn leads to the formation in the structure T-AlMgZn phase. The higher Zn content in the alloy the higher volume fraction of T-AlMgZn phase. The increasing of Zn content in the alloy leads to its increasing in α-Al accordingly. The addition of 1.2–1.8 wt% Zn to the base alloy caused the most significant changes in mechanical properties. Alloying up to 1.2 wt% Zn shows the improvement of strength and hardness while the elongation value remains at the same level as in the base alloy. Alloying with 1.8 wt% Zn shows the highest level of strength (380 MPa of UTS) but the level of elongation decreased. With further increase of Zn concentration the YS and HB continued their growth (up to 270 MPa of YS and 120 HB) whilst elongation and UTS decreased.
Keywords: Al-Mg-Si alloys; Age hardening; Precipitates; Microstructure; Mechanical properties